PENGARUH LATIHAN INTERVAL TRAINING DENGAN RUNNING CIRCUIT TERHADAP PENINGKATAN VO2MAX - Rustiawan, Hendra (Universitas Galuh, 2020)
ABSTRACTThis study aims to determine how much influence the interval training and running circuit training has on Vo2max improvement. Following the objectives of the study above, the authors use the method of pre-experiment with